نجس اجزاء پر مشتمل ادویات کی شرعی حیثیت : منتخب تفاسیر احکام القرآن کی روشنی میں تجزیاتی و تقابلی مطالعہ: The Islamic Legal Status of Medicines Containing Impure (Najis) Ingredients: An Analytical & Comparative Study in the Light of Selected Juristic Exegeses of the Holy Qur’an (Tafāsīr Aḥkām al-Qurʾān) - M Akram ul haque; Dr. Hafiz Muhammad Arshad Iqbal (Al-Amīr Research Journal for Islamic Studies, 2025)
This research paper examines the Shariah status of the use of impure and forbidden ingredients in modern pharmaceuticals. This research is based on the principles of the Qur’an’s prohibition and has been argued by selected exegesis of the Ahkam al-Qur’an. The paper attempts to provide a solution to this complex problem by adopting exegetical, jurisprudential, comparative and analytical research. Key topics of research include the importance of treatment in Islam, the concept of impurity, and the Shariah rules for the use of medicines. The main point of the paper is the application of two important jurisprudential rules–Transformation/Metamorphosis (i.e. the complete change in the nature of the impure substance) and Necessity/Compulsion (permission to use haram in a state of severe compulsion) – to modern pharmaceutical products. In this study, a comparative analysis of the opinions of the Hanafi, Maliki, Shafi’i and Hanbali schools of jurisprudence has been presented and it has been made clear that although the use of medicines containing impure ingredients is forbidden under normal circumstances, in the case of metabolism, when the impure ingredient loses its original nature and is transformed into a new and pure substance, its use becomes permissible. Similarly, when there is a serious threat to the life or health of a patient and there is no halal alternative medicine available, there is a provision for the use of such medicine as required under the Emergency Rule. The paper also presents practical recommendations in the light of the fatwas of the international jurisprudential academies, emphasizing the establishment of international standards for the certification of halal medicines, encouraging pharmaceutical companies to develop halal alternatives, and discharging their responsibilities to Muslim patients and doctors in this regard. The essence of the research is that the principles of Islamic Shariah have the potential to address modern medical challenges, provided they are applied in depth and with insight. Keywords: Islamic Medical Ethics, Halal Pharmaceuticals, Impurity (Najāsah) in Shariah, Istihālah (Transformation), Principle of Necessity (Ḍarūrah), Comparative Fiqh